Belief in Counseling Service Effectiveness and Academic Self-Concept as Correlates of Academic Help-Seeking Behavior Among College Students - Bizuneh, Shambel (Frontiers in Education, 2022)
This study aimed at understanding students’ academic self-concepts, academic help-seeking behaviors, and beliefs in counseling service effectiveness. Based on a correlational research design, a closed-ended questionnaire was administrated to 182 college students. An independent-sample t-test revealed that the average scores of male students were significantly higher than average scores of female students in academic self-concept, help-seeking behavior, and beliefs in counseling effectiveness. An analysis of the relationship between them confirmed that academic help-seeking behaviors, beliefs in counseling service effectiveness, and academic self-concepts significantly correlated with each other. This study also revealed that the variance of academic self-concept and belief in counseling service effectiveness contributed to 36% of the variance in academic help-seeking behavior. Therefore, enhancement projects on academic self-concept and female students’ belief in the effectiveness of counseling services should be taken as an agenda by teachers, college administrators, academic advisors, and counselors.